Determinants of alpha‐fetoprotein levels in patients with hepatocellular carcinoma: Implications for its clinical use. Issue 14 (10th April 2014) - Giannini, Edoardo G.; Sammito, Giorgio; Farinati, Fabio; Ciccarese, Francesca; Pecorelli, Anna; Rapaccini, Gian Lodovico; Di Marco, Mariella; Caturelli, Eugenio; Zoli, Marco; Borzio, Franco; Cabibbo, Giuseppe; Felder, Martina; et al.
<x xml:space="preserve">Abstract</x> BACKGROUND α‐Fetoprotein (AFP) is a biomarker commonly used in the management of patients with hepatocellular carcinoma (HCC), although the possible determinants of its serum levels in these patients have not been adequately explored. For this study, the authors evaluated the relevance of demographic, clinical, and oncologic factors to the presence of elevated AFP levels in large cohort of patients with HCC. METHODS In 4123 patients with HCC who were managed by the Italian Liver Cancer Group, AFP levels were assessed along with their association with demographic, biochemical, clinical, and oncologic characteristics. Patients were subdivided according to the presence of elevated AFP (ie, >10 ng/mL). RESULTS AFP levels were elevated in 62.4% of patients with HCC. Multivariate logistic regression analysis indicated that being a woman (odds ratio [OR], 1.497; 95% confidence interval [95%CI], 1.250‐1.793; P < .0001), the presence of cirrhosis (OR, 1.538; 95% CI, 1.050‐2.254; P = .027), liver disease with viral etiology (OR, 1.900; 95% CI, 1.589‐2.272; P < .0001), an elevated alanine aminotransferase level (OR, 1.878; 95% CI, 1.602‐2.202; P < .0001), a low albumin level (OR, 1.301; 95% CI, 1.110‐1.525; P = .012), an HCC tumor size >2 cm (OR, 1.346; 95% CI, 1.135‐2.596; P = .001), multinodular HCC (OR, 1.641; 95% CI, 1.403‐1.920; P < .0001), and the presence of vascular invasion (OR, 1.774; 95% CI, 1.361‐2.311; P < .0001) were associated independently with elevated levels of AFP. Both the median AFP level and the proportion of patients who had elevated levels increased with decreasing degrees of HCC differentiation (P < .0001). CONCLUSIONS Sex and features of chronic liver disease were identified as nontumor characteristics that influence serum AFP levels in patients with HCC. These findings should be taken into account as limitations in interpreting the oncologic meaning of this biomarker in clinical practice. Cancer 2014;120:2150–2157. © 2014 American Cancer Society.